Liquid crystalline epoxies bearing biphenyl ether and aromatic ester mesogenic units: Synthesis and thermal properties. Issue 5 (4th May 2019) - Chen, Guokang; Zhang, Qian; Hu, Zhuorong; Wang, Shan; Wu, Kun; Shi, Jun; Liang, Liyan; Lu, Mangeng
Abstract: Two liquid crystalline epoxies containing biphenyl ether and aromatic ester mesogenic units, oxybis(4, 1-phenylene)bis(4-(oxiran-2-ylmethoxy)benzoate)(LCE1) and oxybis(4, 1-phenylene) bis(4-(4-(oxiran-2-yl)butoxy)benzoate)(LCE2), were synthesized and characterized. Subsequently, the epoxy monomers were cured with diaminodiphenylsulfone (DDS). From DSC, XRD and POM results, monomers did not show liquid crystalline phase while the cured samples exhibited nematic phase. The cured samples showed good mechanical properties with strength of 99.1MPa and excellent thermal stabilities with high glass transition temperature up to 168.0 °C, 5% weight loss temperature at 343 °C and high char yield of 24.5% at 800 °C. The relationship between thermal conductivity and network structure was discussed in this work. Due to the introduction of mesogenic units into epoxy networks, the cured resins showed high thermal conductivity as high as 0.292 W/(m*K), more than 1.5times higher than conventional epoxy resins. By introducing alumina (Al2 O3 ) into LCE1/DDS cured system, composites of LCE1/DDS/Al2 O3 with the highest thermal conductivity of 1.61 W/(m*K) was obtained with the content of 80 wt% while that of diglycidyl ether of bisphenol A (DGEBA, E51) epoxy resin/DDS/Al2 O3 was 1.10 W/(m*K). The as-prepared epoxy resins showed high glass transition temperature and excellent thermal stabilities, indicating the potential of application in microelectronics.